2022
DOI: 10.3389/feduc.2022.958569
|View full text |Cite
|
Sign up to set email alerts
|

Environmental education and digital solutions: An analysis of the Lebanese context’s existing and possible digital actions

Abstract: One of the main purposes of environmental education is to tackle the youth belief system and raise specific concerns linked to ecology and sustainability. Nonetheless, the educational approach to ecological concerns is partly about the methods used to reach effective results. The advancement of technologies and the rapid spread of social media have accelerated the use of online means of communication. While technology and digital tools have proven effective for educational purposes, it becomes necessary to exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…EL encourages students' environmental perceptions to shift to ecocentric and leave anthropocentric (Weilhoefer & Schmits, 2022). We can say that EE, which has so far been implemented flexibly even during a pandemic, has been able to strengthen aspects of EE (Assaf & Gan, 2021;Brandão & de Souza, 2021;Grežo et al, 2021;Khalifé et al, 2022;Torres Parra et al, 2022). The pandemic period has made many parties aware that EE and EL are so important and should be the concern and commitment of the global community (Benítez et al, 2019;Edsand & Broich, 2020;Marpa, 2020;Reddy, 2021).…”
Section: Results and Discussion Trends In Publications On The Theme O...mentioning
confidence: 99%
“…EL encourages students' environmental perceptions to shift to ecocentric and leave anthropocentric (Weilhoefer & Schmits, 2022). We can say that EE, which has so far been implemented flexibly even during a pandemic, has been able to strengthen aspects of EE (Assaf & Gan, 2021;Brandão & de Souza, 2021;Grežo et al, 2021;Khalifé et al, 2022;Torres Parra et al, 2022). The pandemic period has made many parties aware that EE and EL are so important and should be the concern and commitment of the global community (Benítez et al, 2019;Edsand & Broich, 2020;Marpa, 2020;Reddy, 2021).…”
Section: Results and Discussion Trends In Publications On The Theme O...mentioning
confidence: 99%
“…In this context, the included research focused on different digital tools to achieve SDG 15, out of which Information and communications technology (ICT) and interactive multimedia, including extended reality (VR/AR), video games, video learning, mobile applications, e-books, and online learning are being used. Utilizing the potential benefits of ICT, according to Khalifé et al [12], is urgent to develop students' sustainable development competencies. Dave et al [18] found ICT to be an effective teaching tool in enhancing students' environmental awareness.…”
Section: State Of the Art Of Digital Tools For Fostering Environmenta...mentioning
confidence: 99%
“…This systematic review aims to cover the state of the art of digital tools used in environmental education (EE) to promote sustainability awareness among learners at all stages of learning. Given the relevance of the use of digital educational approaches in strengthening environmental awareness strategies to reduce the severity of environmental complications [12], it is important to investigate the impact of the trend in the use of digital technologies that can benefit educators by providing them with insights into their effectiveness for learning and teaching. Although this field has been covered by Fauville et al [13], no literature review has addressed this topic in the last decade.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental education innovations and studies that have sprung up as an effort to survive amid the COVID-19 crisis/pandemic in 2020 will then be published in the following years. Various existing publications, with trends that tend to increase, provide an overview of how people's responses are to be sure environmental education must be flexible so that it can exist and continue even under the pressure of a pandemic (Assaf & Gan, 2021;Brandão & de Souza, 2021;Grežo et al, 2021;Khalifé et al, 2022;Torres Parra et al, 2022). This is also supported by the fact that environmental education has become a theme of concern and commitment to the global community (Benítez et al, 2019;Edsand & Broich, 2020;Marpa, 2020;Reddy, 2021).…”
Section: Distribution Yearmentioning
confidence: 99%
“…A study is needed regarding the implementation of environmental education according to the needs, expectations and demands of the COVID-19 pandemic era. Study on the theme of environmental education is needed to help find the right form of implementing environmental education and at the same time find the right solution to deal with a pandemic so that environmental education continues to exist (Brandão & de Souza, 2021;Damoah & Omodan, 2022;Khalifé et al, 2022;Otitojua et al, 2022;Probosari et al, 2021) and even plays a role in strengthening literacy and public awareness (Fang et al, 2023;Guo et al, 2022;Iwan et al, 2023;Nurwidodo et al, 2020;Servant-Miklos, 2022).…”
Section: Introductionmentioning
confidence: 99%